The Adoring audience : fan culture and popular media - Lewis, Lisa A. (Routledge, 1992)
"What distinguishes fans from general audiences? Who is most likely to become a fan? This fascinating collection of essays explores the relationship between fans and their adored media products. Examining fandom as a distinct form of cultural activity, an eminent list of contributors discuss a range of topics. "Defining Fandom" assesses the economic, cultural, political, and theoretical positioning of fans. "Fandom and Gender" examines the hysterical response to the Beatles, female fantasies of Elvis and "groupies." "Fans and Industry" considers the extent to which the television industry regards fans as valuable to their enterprise. "Production by Fans" looks at fans as producers of popular culture (fan letters to pop stars and music production by science fiction fans)."--Publisher's description